New Trends in Episodic Memory Assessment: Immersive 360° Ecological Videos - Serino, Silvia; Repetto, Claudia (Frontiers in Psychology, 2018)
How best to measure memory in a reliable and valid way has been intensely debated in neuropsychological literature. Specifically, classical neuropsychological tests often fail to predict real-life performance or capture the multifaceted nature of memory function. To solve these issues, there has been a growing emphasis on the use of more ecological memory assessment. In this scenario, several Virtual Reality based tools have been developed to evaluate memory function. The aim of the current perspective is to discuss critically the possibilities offered for episodic memory assessment by one of the most innovative trends in the technology field, i.e. 360° videos. Immersivity, egocentric view and realism appear to be crucial features of 360° videos enabling them to enhance the ecological validity of classical assessment tools of memory abilities.